The Perception of Slovak Students on Distance Online Learning in the Time of Coronavirus-A Preliminary Study - Petra Poláková; Blanka Klímová (MDPI AG, 2021)
Teaching and learning at educational institutions in Slovakia has been based on traditional education, consisting of face-to-face classes until it was disrupted by the spread of the Coronavirus disease. A sudden lockdown caused massive changes, which presented challenges not only for teachers, but also for students who were forced to adapt their learning in a very short time, without any previous preparation. Since various educational institutions were forced to remain closed, they had no option but to shift from a traditional educational approach to distance learning. This form of education requires a form of online learning. The main purpose of this study was to explore what technical equipment students had at their disposal, to understand the students' perception of distance learning, and to ensure better learning conditions in case of future lockdowns. In order to investigate student readiness for distance learning, a questionnaire survey was conducted at the Secondary Vocational School of Tourism and Gastronomy in Nitra, Slovakia. The findings of this study revealed that the majority of students from the Secondary Vocational School of Gastronomy and Tourism are ready for distance online learning. The results also indicate that a great percentage of students have Internet access and are the owners of technological devices that can be used for educational purposes. Furthermore, students are able to work individually on their own and do not require any help from other people while working on assignments. Although they prefer different teaching methods, the synchronous online courses are their priority because it enables them to have direct contact with their teachers and peers. Overall, this research shows that distance online learning is possible provided that both teachers and students are familiarised with this new learning environment and are ready to cooperate.